Using a game engine to visualize the Main Building of the Warsaw University of Technology in a mobile application - Marciniak Jacek Bernard; Janicki Hubert (Polish Cartographical Review, 2020)
The aim of the study presented in this article is to identify and analyse the problems which arise when creating a 3D model based on two-dimensional data and its import into a game engine and then developing algorithms to automate this process. The authors decided that they would use the Unity game engine to create an application presenting the results of modelling the interior of the Main Building of the Warsaw University of Technology. The work was divided into stages in which problems related to the adopted method were identified and the automation of selected activities was suggested. The main tasks performed during the study included processing the source data into a 3D model along with the correction of errors made during this process, detailing the model by adding characteristic elements of the building’s interior, and creating the so-called game scene in the Unity game engine along with the implementation of the application’s behaviour. The developed software can be integrated with indoor navigation systems, and the implemented scripts can be used during the preparation of other models.